2018
DOI: 10.1155/2018/4012451
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Stress Fields and Crack Growths in the Floor Strata of Coal Seam for Longwall Mining

Abstract: This paper predicts the possibility of water inrush from a confined aquifer under the action of mining activities and water pressure. The study uses numerical analyses to evaluate stress redistribution and crack growth which result from coal extraction operations. Two models are presented in this study. By simplifying the distribution of the disturbed vertical stress on the coal seam and floor around a working face, a model is established to analyze the additional stresses in the floor strata induced by mining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Wang et al revealed the dynamic evolution of cracks and distribution of abutment stress in roof strata under residual pillars using the Voronoi method and proposed some measures to ensure safety in longwall mining (Wang et al, 2019). Additional stress distribution of the floor strata was presented, and the stress intensity factors for the cracks at different positions were obtained to predict crack growths in confined aquifers in floor strata (Sun et al, 2018). Liu et al established a floor stress-solving mechanics model of the oblique seam, and the maximum damage depth in the floor was obtained by theoretical calculations, numerical simulations, and a site experiment using a borehole leak detection device (Liu et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…Wang et al revealed the dynamic evolution of cracks and distribution of abutment stress in roof strata under residual pillars using the Voronoi method and proposed some measures to ensure safety in longwall mining (Wang et al, 2019). Additional stress distribution of the floor strata was presented, and the stress intensity factors for the cracks at different positions were obtained to predict crack growths in confined aquifers in floor strata (Sun et al, 2018). Liu et al established a floor stress-solving mechanics model of the oblique seam, and the maximum damage depth in the floor was obtained by theoretical calculations, numerical simulations, and a site experiment using a borehole leak detection device (Liu et al, 2017).…”
Section: Figurementioning
confidence: 99%
“…Yushen Coalfield is located in the transition zone between the Loess Plateau and the Mu Us Sandy Land with rugged topography, and a gullied surface [9], under gullies topography, mining-induced surface cracks is a severe threat to the local fragile ecological environment [10][11][12][13]. Researchers have studied the influence of valley topography on mining-induced surface cracks using numerical simulation [14][15][16][17],…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above simulation experimental results and theoretical analysis, it can be found that the development of surface cracks in double gullies terrain is affected by geological conditions, gully depth, slope, valley span and other factors. According to the theory of mining slip, and considering the basic parameters of the gully, the relative position function T and discriminant conditions of surface cracks development in shallow coal seam mining through double gullies terrain can be obtained, as shown in formulas (15) and(16).…”
mentioning
confidence: 99%
“…In particular, the variations of elastic modulus and Poisson's ratio with depth are considered. e numerical method used for analysis is developed by applying the fundamental solution of layered elastic solids [10][11][12][13][14][15][16][17] and integrating it over the loading area. e adaptive numerical quadrature and parallel computation techniques are used to evaluate the integrals over the elements on the discretized area.…”
Section: Introductionmentioning
confidence: 99%